DETERMINATION OF MAINTENANCE FACILITY LOCATIONS AND IMPROVEMENTS TO SUPPORT THE OPERATION OF INDONESIAN NAVY IN NORTH NATUNA SEA BY THE FUZZY MCDM METHODS - Okol Sri Suharyo; Edy Widodo; Didit Herdiawan; Joko Purnomo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Support the presence of the KRI elements it needs other supporting means such as Fasharkan (Maintenance and repair facilities) that serve as a supporter of logistics, especially repair and maintenance of KRI. The closest area of Fasharkan from the Sea of North Natuna today is Fasharkan Mentigi Lantamal IV Tanjung Pinang is approximately 510 Nm surely will be an obstacle when the presence of the KRI element in the North Natuna Sea operating area is shaken because The distance of Fasharkan from the distant waters of North Natuna to carry out maintenance and repair. So it is necessary to one more location of Fasharkan to support the operation of the KRI elements in the territorial waters of North Natuna so that the operation of the KRI elements can be carried out well. In the selection of Fasharkan location has several factors that must be considered so that categorized have multicriteria in the election. So to accommodate Multicriteria divided into Technical Requirements & Operational Requirements Then use the Fuzzy method MCDM (Multi-Criteria Decision Maker). Technical Requirement consisting of earthquake hazard, distance field operations (distance operations and ALKI 1), distance downtown (the distance of the center of the government and the settlement), and hydrography (depth, tidal, and speed of currents). While the Operational Requirement consists of the influence of other countries, threats (outside state threat and community conflicts), access transportation (military port and airport), supporting facilities (water facility, communication facilities, Electric facilities, transport facilities and sea flows), as well as operational costs. For the alternative location of Fasharkan consists of Lantamal XII Pontianak, Ranai Navy Base, and Tarempa Navy Base.Of the three alternative locations obtained the best alternative to the location of Fasharkan is Ranai Navy Base with the highest rank of 0.403 then Lantamal XII Pontianak with a value of 0.302 and Tarempa Navy base with a value of 0.295. Keywords: Sea of North Natuna, Fasharkan, determination of the type of Fasharkan, determining thelocation of the Fasharkan, Fuzzy MCDM.